Behavior of Chinese Tourist Travelers Visiting Pattaya City - อ้นยะ, ภณสิทธ์; โตสัจจะวงษ์, จรูญวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aims to study the tourism behavior of Chinese tourists visiting Pattaya City by considering demographic characteristics, travel behavior, and factors influencing their decision to choose tourist destinations. Furthermore, the study proposes strategies for developing the tourism industry to align with the needs of this group. The research employs quantitative methods, collecting data from a sample of 400 Chinese tourists through questionnaires.The findings reveal that the majority of Chinese tourists are male, aged between 31-45 years, hold a bachelor's degree, and work as private company employees. Their average annual income ranges between 80,000 - 100,000 yuan. The study shows that most tourists visit Pattaya for leisure and tend to return each time they visit Thailand. Popular destinations include night markets, entertainment venues, and beaches. Most tourists plan their trips independently, with decisions influenced by family members.          In terms of spending behavior, most tourists spend over 2,000 yuan per trip and prefer accommodations such as 2-3 star hotels. For transportation within Pattaya, they commonly use rental cars or taxis. Many also travel to other provinces in Thailand, such as Chiang Mai. Additionally, most tourists do not require guides or interpreters during their trips and express intentions to revisit Pattaya in the future.          Based on the findings, recommendations for developing Pattaya's tourism industry include improving tourism infrastructure to meet the needs of Chinese tourists, enhancing accessible promotional channels, and tailoring services to align with the behavior and expectations of this group.